The Anxiety in English Speaking Experienced by Students in a Designated Private Junior High School - Simanungkalit, Ate Gueen (SUMIKOLAH: Jurnal Ilmu Pendidikan, 2024)
Anxiety in English Speaking Experienced by Students in a Designated Private Junior High School in Minahasa Utara Ate Gueen Simanungkalit Mentari M. P. Tondombala agsimanungkalit@unklab.ac.id Abstract In the process of learning English, students often encounter speaking anxiety as a significant challenge. This type of anxiety involves various concerns when speaking a foreign language, such as nervousness about communication, fear of tests, and worry about being judged negatively. The primary objective of this study was to assess the extent of speaking anxiety experienced by students. Data was gathered from 83 seventh-grade students at a designated private junior high school in Minahasa Utara, Indonesia. The study employed a quantitative approach and utilized a 5-point Likert scale questionnaire adapted from Natalia (2014), originally developed by Horwitz, Horwitz, and Cope (1986), to measure students' English-speaking anxiety. The results indicated that, overall, students had a moderate level (M = 2.87; SD = 0.50) of speaking anxiety. Notably, the most prevalent form of speaking anxiety among students was the fear of negative evaluation (M = 2.99; SD = 0.67). It was recommended, among others, that the English teachers create a non-judgmental classroom environment to encourage voluntary student participation, provide test preparation to ease test-related anxiety, and future research should aim for larger and more diverse samples to gain a deeper understanding of student speaking anxiety. Keywords -- English speaking anxiety, fear of negative evaluation, junior high school. Abstrak Dalam proses pembelajaran bahasa Inggris, siswa sering menghadapi kecemasan berbicara sebagai tantangan besar. Jenis kecemasan ini melibatkan berbagai perasaan cemas saat berbicara dalam bahasa asing, seperti rasa gugup dalam berkomunikasi, ketakutan akan ujian, dan kekhawatiran tentang penilaian negatif. Tujuan utama dari penelitian ini adalah untuk menilai sejauh mana kecemasan berbicara yang dialami oleh siswa. Data dikumpulkan dari 83 siswa kelas tujuh di sebuah sekolah menengah pertama swasta yang ditunjuk di Minahasa Utara, Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dan menggunakan kuesioner skala Likert 5 poin yang diadaptasi dari Natalia (2014), yang awalnya dikembangkan oleh Horwitz, Horwitz, dan Cope (1986), untuk mengukur kecemasan berbicara dalam bahasa Inggris siswa. Hasil penelitian menunjukkan bahwa secara keseluruhan, siswa memiliki tingkat kecemasan berbicara yang sedang (M = 2,87; SD = 0,50). Yang paling umum adalah bentuk kecemasan berbicara di antara siswa adalah ketakutan akan penilaian negatif (M = 2,99; SD = 0,67). Disarankan, antara lain, bahwa guru bahasa Inggris menciptakan lingkungan kelas yang bebas penilaian untuk mendorong partisipasi sukarela siswa, memberikan persiapan ujian dengan memberikan sumber daya tambahan guna mengurangi kecemasan ujian, dan penelitian masa depan sebaiknya menggunakan sampel yang lebih besar dan lebih beragam untuk memperoleh pemahaman yang lebih mendalam tentang kecemasan berbicara siswa. Kata kunci -- kecemasan berbicara dalam bahasa Inggris, ketakutan akan penilaian negatif, sekolah menengah pertama.